Characterisation and screening of antimicrobial essential oil components against clinically important antibiotic‐resistant bacteria using thin layer chromatography‐direct bioautography hyphenated with GC‐MS, LC‐MS and NMR - Owen, Lucy; White, Alex W.; Laird, Katie (Phytochemical analysis, 2019)
Introduction The antimicrobial activity of many essential oils (EOs) is well established, indicating that EOs may be a source of compounds for antimicrobial drug development. Thin layer chromatography‐direct bioautography (TLC‐DB) can quickly identify antimicrobial components in complex mixtures and can be applied to the screening of EOs for lead compounds. Objectives This study aimed to identify antimicrobial components of oregano, rosewood and cumin EOs against antibiotic‐sensitive and ‐resistant bacteria using TLC‐DB and a multi‐faceted approach of GC‐MS, LC‐MS and NMR techniques to characterise bioactive compounds. The study also aimed to quantify the antimicrobial activity of bioactive compounds in order to evaluate their potential for the development of therapies against antibiotic‐resistant bacteria. Materials and Methods EOs were eluted on TLC plates and sprayed with a suspension of Staphylococcus aureus, Enterococcus faecium, Escherichia coli or Pseudomonas aeruginosa (antibiotic‐sensitive and ‐resistant isolates). Zones of inhibition, visualised with iodonitrotetrazolium chloride, were subject to GC‐MS, LC‐MS and NMR to characterise the bioactive compounds. Results Seven compounds were identified from the three EOs using GC‐MS, while LC‐MS and NMR failed to detect the presence of any further non‐volatile or heat labile compounds. Carvacrol was most antimicrobial compound identified, with minimum inhibitory concentrations ranging 0.99–31.62 mM. Conclusion The identified antimicrobial compounds present in oregano, rosewood and cumin EOs including carvacrol may be candidates for the development of novel antimicrobial therapies against antibiotic‐resistant bacteria. In this study, components of oregano, rosewood and cumin essential oils with antimicrobial activity against antibiotic‐sensitive and ‐resistant bacteria were identified using thin layer chromatography‐direct bioautography (TLC‐DB) coupled with GC‐MS, LC‐MS and NMR as a multi‐faceted approach for the characterisation of antimicrobial essential oil fractions. Carvacrol was the most antimicrobial compound identified, with minimum inhibitory concentrations ranging from 0.99 to 31.62 mM, and may be a candidate for the development of therapies against antibiotic‐resistant bacteria.